2011
DOI: 10.1128/aac.01430-10
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pharmacokinetic-Pharmacodynamic Analyses To Optimize Therapy with the Systemic Antifungal Micafungin for Invasive Candidiasis or Candidemia

Abstract: were examined. Micafungin exposures were estimated using a population pharmacokinetic model, and univariable and multivariable logistic regressions were used to identify factors associated with outcome, including the micafungin area under the concentration-time curve (AUC)/MIC ratio. Monte Carlo simulation was used to evaluate the probability of achieving AUC/MIC ratios associated with efficacy. Mycological and clinical success rates for evaluable cases were 89.4 and 90.9, respectively. MIC 50 s and MIC 90 s f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
100
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 45 publications
9
100
3
Order By: Relevance
“…This is not a surprise, given the BMI categories we examined (1), in which the proportions of overweight and obese people mirror those of the American public. The population pharmacokinetic parameter estimates for our "healthy" volunteers were virtually identical to those determined for patients with fungal infections in studies published in the past (2,9,11,26), which suggests that our findings likely have relevance even for patients with fungemia.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This is not a surprise, given the BMI categories we examined (1), in which the proportions of overweight and obese people mirror those of the American public. The population pharmacokinetic parameter estimates for our "healthy" volunteers were virtually identical to those determined for patients with fungal infections in studies published in the past (2,9,11,26), which suggests that our findings likely have relevance even for patients with fungemia.…”
Section: Discussionsupporting
confidence: 63%
“…Micafungin concentrations were modeled using the ADAPT 5 program of D'Argenio and colleagues (5). Based on prior work, micafungin is known to follow two-compartment model pharmacokinetics in humans (2,9,12). Therefore, a two-compartment model with first-order input and elimination was utilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of therapy in our cohort might be driven by pathogens with low MICs (Ͻ0.03 mg/liter), which would result in 100% target attainment. However, data on susceptibility are lacking in this research, and conclusions on the exposure response in relation to the susceptibility of the pathogen as drawn by Andes et al (40) cannot be substantiated.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, Andes et al (40) demonstrated by analysis of two micafungin phase III trials that the probability of mycological cure in adult patients with invasive candidiasis or candidemia receiving micafungin therapy (55% were admitted to the ICU) was higher if the patient attained an AUC/MIC ratio between 3,000 and 12,000 compared to a ratio of Ͻ3,000 (98.0% versus 85.1%, respectively). The authors concluded that if the MIC was Ͻ0.06 mg/liter, the vast majority of the patients would attain the lower target of 3,000 (11,12,40). A subgroup analysis of the 55% ICU patients in this cohort is lacking in this paper.…”
Section: Discussionmentioning
confidence: 99%